SOCIAL ISSUES AND ITS IMPACT PRESENTED IN NOMADLAND (2022): A MARXIST PERSPECTIVE - Listiyani, Della; Anggraeni, Diana; Fitri K., Dian (Smart Edu Center, 2025)
This study examines the film Nomadland through the lens of Karl Marx’s Marxist theory, focusing on the dynamics of social class, economic exploitation, and class conflict represented in its narrative. The research seeks to uncover how social transformations affect both primary and secondary characters, while also assessing the relevance of Marxist theory in the context of contemporary society. Employing a descriptive qualitative approach, the analysis highlights the portrayal of social issues and their influence on the characters’ lives. The findings reveal two central issues from a Marxist perspective: social class injustice and labor exploitation, as reflected in the film’s narrative, dialogue, and characterization. Moreover, the study identifies two significant consequences: alienation—both self-alienation and labor alienation—and the lived experience of modern nomadic life.